The Need For Repeated Measurement Designs In Organizational Research - Brightman, Harvey J. (Academy of Management Journal, 1971)
In educational and psychological research, the Before-After experiment has been the classical design. The purpose of this paper is to discuss two major limitations of the design for organizational research. In contrast to educational research, the timing of the ?after? measurements is not always apparent. Second, the ?Before-After? designs do not yield the time series data necessary for developing lead-lag models relating two or more organizationally relevant variables. It is suggested that this information can be useful in the day-to-day operational control of the organization. The repeated measurements design is suggested as an appropriate alternative.